Utilization of Digital Technologies in Promoting Research Skills of Postgraduate Students: A Case Study of Ebonyi State University, Abakaliki - Nwajioha , Patrick N; Ede , Francisca N.; Agwu, Lydia O.; Tochuckwu , Chukwu; Ogene, Amaka F. (Journal of Home Economics Research, 2024)
The study focused on issues relating to digital technologies and research skills of postgraduate students in Ebonyi State University, Abakaliki. Specifically, it determined; digital technologies necessary and available for developing research skills among postgraduate students in EBSU, factors that militate against the utilization of digital technologies for promoting research skills among postgraduate students in EBSU and ways of ameliorating challenges of utilization of digital technologies for promoting research skills among postgraduate students in EBSU. A survey research design was adopted. Population was 1,189; comprising of 565 lecturers and 624 postgraduate students of three academic years (2020/2021, 2021/2022 and 2022/2023 sessions) in Ebonyi State University, Abakaliki. Data were analyzed using mean and standard deviation. Findings of the study include 13 digital technologies (DT) necessary for developing research skills among postgraduate students in EBSU. These include, among others, projectors ( X = 3.26), laptops ( X = 3.53), desktop computers ( X = 3.79), printer machines ( X = 3.70). Only four of the DTs are availability, desktop computers ( X = 3.79), printer machines ( X = 3.70), photocopier machines ( X = 3.44) and scanners ( X= 3.37). Also nine challenges were identified, including inadequate number of computers to access digital information ( X = 3.31), lack of skills to access digital information resources among students ( X = 3.20), inadequate hardware and software (X = 3.11) and others. Furthermore, nine ways of ameliorating the challenges, including promoting internet connectivity and requisite subscription to address the challenges of inadequate computers to increase access to digital information (X = 2.92) promoting environmental friendliness for critical thinking in the university ( X = 3.12) and others. Three recommendations were made for utilization of DT in promoting research skills of postgraduate students in EBSU.